2020
DOI: 10.3390/ijms21249447
|View full text |Cite
|
Sign up to set email alerts
|

Serine Racemase Deletion Affects the Excitatory/Inhibitory Balance of the Hippocampal CA1 Network

Abstract: d-serine is the major co-agonist of N-methyl-D-aspartate receptors (NMDAR) at CA3/CA1 hippocampal synapses, the activation of which drives long-term potentiation (LTP). The use of mice with targeted deletion of the serine racemase (SR) enzyme has been an important tool to uncover the physiological and pathological roles of D-serine. To date, some uncertainties remain regarding the direction of LTP changes in SR-knockout (SR-KO) mice, possibly reflecting differences in inhibitory GABAergic tone in the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
0
15
1
Order By: Relevance
“…The lack of apparent seizure activity with the increase E/I ratio further suggests concurrent homeostatic processes, though we cannot rule out covert temporal lobe epileptiform bursting in the SRKO mice. Furthermore, other compensatory mechanisms could contribute to the normalization of LTP in the SRKO mice, including an increase in hippocampal glycine levels (109), and an increased in synaptic GluN2B (53,64). Overall, these homeostatic changes suggest that there is a prioritization of synaptic and cellular functions over network function resulting in a disruption of the signalto-noise ratio and impairing cognition.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of apparent seizure activity with the increase E/I ratio further suggests concurrent homeostatic processes, though we cannot rule out covert temporal lobe epileptiform bursting in the SRKO mice. Furthermore, other compensatory mechanisms could contribute to the normalization of LTP in the SRKO mice, including an increase in hippocampal glycine levels (109), and an increased in synaptic GluN2B (53,64). Overall, these homeostatic changes suggest that there is a prioritization of synaptic and cellular functions over network function resulting in a disruption of the signalto-noise ratio and impairing cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies of SRKO mice can confirm whether (1) the abnormal biomarker phenotypes persist among antipsychotic or D-serine treatment, (2) glycine-related compensatory responses are occurring, (3) thalamocortical circuitry is intact, or (4) abnormalities in dopamine levels, cholinergic signaling, or parvalbumin-containing neurons exist in the neocortex. Recent work indicates SRKO mice have reduced inhibitory tone in hippocampal networks which disrupts neural synchrony and the E/I balance 72,73 . This, along with our gamma band findings support the idea of an E/I imbalance manifested as an aberrant signal-to-noise ratio impairing cognition and information processing.…”
Section: Discussionmentioning
confidence: 99%
“…Through the coordinated activities of ASC-1 and ASCT1 subtypes, D-serine is released and binds with NMDAR to perform neurophysiological functions (Sason et al, 2017;Billard, 2018;Kaplan et al, 2018). The deletion of SR affects the balance of excitatory and inhibitory in the hippocampal CA1 network (Ploux et al, 2020). In addition, related research has found that PKC phosphorylates SR on serine residues and reduces the activity of SR in vitro.…”
Section: D-serinementioning
confidence: 99%
“…Endogenous D-serine deficiency may lead to decreased inhibition of the hippocampal CA1 network and altered excitatory/inhibitory balance. besides, D-serine contributes to maintaining cognitive abilities and functional plasticity of synapses (Ploux et al, 2020). Related studies have shown that intracranial injection of D-serine into the medial entorhinal area (MEA) in the TLE is beneficial to prevent neuronal loss and epileptogenesis by rescuing hippocampal CA1 neurons in the epileptic brain and reducing the number of astrocytes and microglia, thus alleviating the effect of neuroinflammation (Beesley et al, 2021).…”
Section: D-serinementioning
confidence: 99%